The Phytochemical and Biological Activities of Two Phyllanthus Species: Insights into Metabolit, Antioxidant and Antibacterial Activity - Araújo, Otilda Fátima; Kristiani, Elizabeth Betty Elok; Kasmiyati, Sri; Nugroho, Laurentius Hartanto (Biosaintifika: Journal of Biology & Biology Education, 2024)
Phylanthus species, including P. niruri and P. urinaria have pharmacological potential due to their rich phytochemical composition. People usually used this plant for medicinal treatments. This study aimed to compare the phytochemical and antioxidant and antibacterial activities of two Phyllanthus species. The whole of plants was extracted using maceration method with ethanol as solvent. Phytochemical content analyzed using spectrophotometer.  The reagent used for each compounds that were Folin-ciocalteu for phenolics, AlCl3 for flavonoid, dimethyl sulfoxide for chlorophyll and carotenoid. Bioactivity analysis using 1,1-diphenyl-2-picrylhydrazyl method for antioxidant activity and Kirby-Bauer method for antibacterial activity. The highest flavonoid content (12.22 mg QE/gram extract) and total chlorophyll (43.2 µg/ml extract) in P. niruri while phenolic content (80.8 mg GAE/gram extract) in P. urinaria. The carotene of both Phyllanthus were similar (11.9 µg/ml extract. The IC50 values of P. urinaria (6.16 ± 0.42 μg/ml) and P. niruri (17.72 ± 0.80 μg/ml), which indicated very strong antioxidant activity. P. urinaria leaf extract had stronger inhibition against Escherichia coli than Staphylococcus aureus (>20 mm) and P. niruri leaf extract could inhibit E. coli and S. aureus bacteria at all concentrations (11-20 mm). This study found that phenolic compounds strongly influenced the antioxidant and antibacterial abilities of Phyllanthus, while chlorophyll and carotenoids had only a slight influence. These findings open up opportunities to utilize P. niruri and P. urinaria as antioxidant and antibacterial agents.